IMPROVED APIP PERFORMANCE THROUGH TRAINING, INFORMATION TECHNOLOGY, INDEPENDENCE AND OBJECTIVITY IN KLATEN DISTRICT INSPECTORATE - Nining Martiningsih; Istiatin Istiatin; Sudarwati Sudarwati (University of Islam Malang, 2022)
This research looks at the influence of training, information technology, independence, and objectivity on the Performance of the Local Government Internal Supervisory Apparatus (APIP) on the Klaten District Inspectorate by data collection using questionnaires and observations and documentation. The population in this study was the klaten district inspectorate of 54 employees. The sample taken in this study was as many as 54 employees of the Klaten County Inspectorate. The analysis tool in this study is multiple linear regression using SPSS 24. From the results of the study conclusions as follows, training has a positive but not significant effect on the performance of APIP Klaten Regency. Information technology, Independence and Objectivity have a positive and significant effect on the performance of APIP Klaten Regency.